THE FUNCTIONS OF THE PREAMBLE OF THE CONSTITUTION AND THE CHARACTERISTICS OF THE PREAMBLE OF THE CONSTITUTION OF THE REPUBLIC OF SERBIA - Simović, Darko Z (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Contrary to the normative part of the constitution whose basic function is of legal character, the preamble of the constitution is characterized primarily by sociological functions. There are many of them, however they are intertwined, hence one sociological function, as a rule is tied to the majority of other sociological functions. However, it is possible for certain functions of the preamble to be in collision. Based on a comparative analysis of modern constitutions we can discuss the following sociological functions of the preamble of the constitution: symbolic, legitimacy, integrative, ideological, educational and programmatic. Aside from sociological functions, the preamble can also have, although more rarely, a legal function. With respect to the preamble of the Constitution of the Republic of Serbia, its content is directed at establishing the territorial identity of the country. In that sense, it can be concluded that the symbolic function of the preamble of the Constitution is more dominant. Although in its content it does not offer anything new in relation to the normative part of the constitution, it announces in a celebratory tone, that Kosovo and Metohija are an integral part of the Republic of Serbia.